INNOVATIVE PEDAGOGICAL ACTIVITY AS A DRIVING FORCE OF EDUCATIONAL DEVELOPMENT OF THE XXI CENTURY - Khmurova, Viktoriia Valentynivna; Nazarova, Mariam Mariia (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2021)
The main purpose of scientific research is to highlight pedagogical activities as one of the most important factors in the innovative development of education in the age of information technology. The article provides brief information about pedagogical innovations and innovation processes. We paid special attention to the skills that a modern teacher should have.